Processes of code status transitions in hospitalized patients with advanced cancer. Issue 24 (7th September 2017) - El‐Jawahri, Areej; Lau‐Min, Kelsey; Nipp, Ryan D.; Greer, Joseph A; Traeger, Lara N.; Moran, Samantha M.; D'Arpino, Sara M.; Hochberg, Ephraim P.; Jackson, Vicki A.; Cashavelly, Barbara J.; Martinson, Holly S.; Ryan, David P.; et al.
Abstract : BACKGROUND: Although hospitalized patients with advanced cancer have a low chance of surviving cardiopulmonary resuscitation (CPR), the processes by which they change their code status from full code to do not resuscitate (DNR) are unknown. METHODS: We conducted a mixed‐methods study on a prospective cohort of hospitalized patients with advanced cancer. Two physicians used a consensus‐driven medical record review to characterize processes that led to code status order transitions from full code to DNR. RESULTS: In total, 1047 hospitalizations were reviewed among 728 patients. Admitting clinicians did not address code status in 53% of hospitalizations, resulting in code status orders of "presumed full." In total, 275 patients (26.3%) transitioned from full code to DNR, and 48.7% (134 of 275 patients) of those had an order of "presumed full" at admission; however, upon further clarification, the patients expressed that they had wished to be DNR before the hospitalization. We identified 3 additional processes leading to order transition from full code to DNR acute clinical deterioration (15.3%), discontinuation of cancer‐directed therapy (17.1%), and education about the potential harms/futility of CPR (15.3%). Compared with discontinuing therapy and education, transitions because of acute clinical deterioration were associated with less patient involvement ( P = .002), a shorter time to death ( P < .001), and a greater likelihood of inpatient death ( P = .005). CONCLUSIONS: One‐half of code status order changes among hospitalized patients with advanced cancer were because of full code orders in patients who had a preference for DNR before hospitalization. Transitions due of acute clinical deterioration were associated with less patient engagement and a higher likelihood of inpatient death. Cancer 2017;123:4895‐902 . © 2017 American Cancer Society . Abstract : Most hospitalized patients with advanced cancer do not have a code status discussion upon admission, and not eliciting patients' cardiopulmonary resuscitation preferences at the time of admission is the most common cause of code status order change from full code to do not resuscitate. Educating patients about the potential harms of cardiopulmonary resuscitation is an important process leading to code status transitions earlier in the course of illness.